The Incidence of Tiphoidal Salmonellosis in Pediatric Department of Shkodra Regional Hospital Diuring the Period January – December 2010 - Shabani, Zamira; Shpori, Manjola; Qirjako, Gentiana (Mediterranean Journal of Social Sciences, 2012)
Typhoid fever is a systemic disease characterized by fever and abdominal pain caused by dissemination of S. typhi or S.paratyphi. In contrast to other Salmonella serotypes, the etiologic agents of enteric fever (S. typhi and S. paratyphi) have unknown hostsother than humans. Thus, enteric fever is transmitted only through close contact with acutely infected individuals or chronic carriers.Rather, most cases of disease result from ingestion of contaminated food or water. Over the past four decades, with the advent ofimprovements in food handling and water/sewage treatment, enteric fever has become a rare occurrence in developed nations. Childrenunder 1 year of age appear to be most susceptible to initial infection and to the development of severe disease. Enteric fever is endemicin most developing regions and is related to rapid population growth, increased urbanization, inadequate human waste treatment, limitedwater supply, and overburdened health care systems. Morbidity and mortality are increased in outbreaks associated with antibioticresistantstrains, presumably because of inadequate or delayed treatment. In this article we have considered all hospitalized cases inpediatric department of Regional Hospital of Shkodra, with acute diarrhea. All cases diagnosed as salmonelosis typhoid’s and portablesare diagnosed with culture proven because we don`t effort the serology method cause of expensive kits and provisions) in our hospitals.It is impossible to have this information because the hospital has not the high technology laboratory. It has very old equipments in thecurrent laboratories and we use only the culture proven instead. The elaboration of datas is made by a simple method, descriptiveand cumulative. Some dates analyzed with Microsoft Office Excel method are presented through graphics.